Promoting stewardship of forests in the humid forest zone of Anglophone West and Central Africa: Final Report of a collaborative research project undertaken by the UNEP and CIFOR - Dykstra, D.P.; Kowero, G.S.; Ofosu-Asiedu, A.; Kio, P. (1996)
A UNEP-sponsored project, implemented by CIFOR focused on the West African humid forests of Ghana and Nigeria. Liberia, Sierra Leone and Cameroon also were included in the study. The general objective of the project was to integrate all available information on humid forest formations in this region in order to promote initiatives to foster the adoption of sustainable forest management principles. The report is organised into nine chapters. The first chapter gives an account of the forestry situation in West and Central Africa, with emphasis on vegetation distribution and factors affecting forest management. Chapters 2 and 3 highlight past and present silvicultural and forest management practices and also consider management control systems. The relevance of biodiversity and the role of non-timber forest products are explored in Chapter 4. Inter-generational issues, socio-economic factors influencing sustainable forest management, and the relevance of policies and legislation are addressed in Chapters 5, 6 and 7. Chapter 8 outlines strategies and incentives which might be adopted to promote sustainable forest management. The report concludes with suggestions for research which could be undertaken to fill gaps in knowledge which became apparent in the course of this project. The project contributes to a larger joint project currently being undertaken by CIFOR and the Government of France for the Francophone countries of Côte d'Ivoire, Cameroon, Central African Republic, Congo and Gabon.